PERMASALAHAN GURU DAN BANTUAN YANG DIBERIKAN SUPERVISOR - Rahma Dwi Putri; Silvia Rahmayani; Jamilus; Anis mahatika (JIP: Jurnal Ilmu Pendidikan, 2024)
The problems faced by teachers in the learning process are challenges that affect the quality of education. These problems include a lack of pedagogical competence, difficulties in managing classes, and a lack of understanding of the curriculum. In an effort to overcome this, the role of educational supervisors is very important. Supervisors act as mentors, providing support in the form of advice, training and mentoring to teachers to improve their professional abilities. This study aims to analyze the types of problems faced by teachers and the effectiveness of assistance provided by supervisors in supporting increased teacher competency. The results of the research show that continuous supervision and based on teacher needs is able to have a positive impact on teacher performance, thus contributing to improving the quality of learning in schools